Injuries in professional women`s elite soccer players in Kosovo: epidemiological injury study - Gashi, F.; Kovacic, T.; Shalaj, I.; Haxhiu, B.; Boshnjaku, A. (BMC Sports Science, Medicine and Rehabilitation, 2023)
Background An emphasis has been given lately towards women`s engagement together with their potential in soccer. As this sport develops with athletes becoming more physically fit and skilled, it is unclear what the consequences in terms of injuries are. Having this in mind, this study aimed to investigate the major injuries that occur in women`s soccer players.